2005
DOI: 10.1590/s0103-84782005000300030
|View full text |Cite
|
Sign up to set email alerts
|

Substituição de farinhas de origem animal por ingredientes de origem vegetal em dietas para frangos de corte

Abstract: Devido às exigências de alguns importadores, por motivação cultural ou devido a zoonoses recém acontecidas na Europa, tem havido um direcionamento para fabricação de rações vegetais com base em milho e farelo de soja (FS). Esse direcionamento traz conseqüências na produção e por isso, objetivou-se avaliar a resposta de frangos de corte alimentados com dietas contendo farinhas de carne e ossos (FCO) e farinha de vísceras de aves (FV) e dietas contendo milho e FS. As dietas foram calculadas para conterem 3.050 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
2
13
1
2
Order By: Relevance
“…Unlike the results observed in this experiment, Bellaver et al (2001) observed that diets with 5% of viscera and bone meal in substitution of soybean meal resulted in better broiler performance in the growing phase, but diets with 3% of viscera and bone meal did not affect performance until 21 days of age (Bellaver et al, 2005). Laboissiere (2008) verified that the best performance in the pre-starter phase was achieved with 9.0% of viscera and bone meal obtained from different processing systems (varying cooking temperature and moisture).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the results observed in this experiment, Bellaver et al (2001) observed that diets with 5% of viscera and bone meal in substitution of soybean meal resulted in better broiler performance in the growing phase, but diets with 3% of viscera and bone meal did not affect performance until 21 days of age (Bellaver et al, 2005). Laboissiere (2008) verified that the best performance in the pre-starter phase was achieved with 9.0% of viscera and bone meal obtained from different processing systems (varying cooking temperature and moisture).…”
Section: Resultscontrasting
confidence: 99%
“…Including animalorigin byproducts in poultry diets can cause an amino acid imbalance, mainly in the non-essential ones (MacLeod, 2001) if their levels are not analyzed. However, these ingredients can result in low feed cost, especially when the ideal protein concept based on digestible amino acids is used (Vieites et al, 2000;Bellaver et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…These ingredients contain amino acids, energy, calcium and phosphorus in balanced amounts. In practical view, for nutritionists, animal origin by-products and fats which are substituted by vegetable oil, soybean meal and dicalcium phosphate and other supplements can result in higher feeding costs (Bellaver et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments performed by Longo et al (2005), performance of chicks in pre-starter ration was not affected by the protein source fed, but this effect did not persist in the subsequent raising period. Rations containing these ingredients, when formulated based on ideal protein concept, result in better broiler performance (Cancherini et al, 2004;Bellaver et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Muitos importadores da carne de frango brasileira, como a União Européia e o Oriente Médio, exigem que as aves não recebam alimentação com ingredientes de origem animal nem promotores de crescimento (Bellaver et al, 2005), o que direciona para a produção de animais alimentados com rações estritamente vegetais.…”
Section: Introductionunclassified